2016
DOI: 10.1016/j.renene.2015.07.036
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the evaluation of natural ventilation performance of a two-sided wind-catcher for various wind angles

Abstract: a b s t r a c tNatural ventilation performance of a two-sided wind-catcher is investigated for various wind angles (a ¼ 0 e90 ) and wind speeds by experimental wind tunnel and smoke flow visualization. A 1:50 scale model of a real wind-catcher in the city of Yazd (Iran) is employed. The pressure coefficient as well as velocity are measured by pressure taps and hot-wire anemometer, respectively. The hot-wire results are used to evaluate the induced airflow rate and turbulence intensity. Smoke flow visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Different researchers studied the ventilation performance of two-sided windcatcher as well as other types of windcatcher by wind tunnel testing and numerical method [5], [21] and [14]. In addition, few investigations evaluated the performance of wing wall -alone-for natural ventilation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Different researchers studied the ventilation performance of two-sided windcatcher as well as other types of windcatcher by wind tunnel testing and numerical method [5], [21] and [14]. In addition, few investigations evaluated the performance of wing wall -alone-for natural ventilation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Afshin et al [5] investigated ventilation performance of a two-sided windcatcher for different wind angles ( from 0° to 90°) by wind tunnel experiment. A 1:50 reduced-scale model of a conventional two-sided windcatcher in the city of Yazd (Iran) was modeled.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Afshin et al [22] also investigated the natural ventilation performance of a two-sided windcatcher for various wind angles using wind tunnel and smoke testing. The smoke testing revealed that the air streams towards the bottom of the windcatcher channel are divided into two; the first stream tends to move to the room below.…”
Section: Short-circuitmentioning
confidence: 99%
“…(3) Natural ventilation: To implement nZEB, an architectural design for inducing the reduction of the building energy demand through the effective influx of the outdoor air (i.e., natural ventilation) should be considered in the initial design stage. Generally, natural ventilation can be categorized based on two mechanisms: (i) buoyancy-driven ventilation by the vertical and horizontal temperature difference; and (ii) wind-driven ventilation by the pressure difference between the front and the back of the building (refer to Table 3) [29][30][31][32][33][34][35][36][37][38]. First, there are various previous studies related to buoyancy-driven ventilation [29][30][31][32][33][34].…”
Section: Part A-1: Passive Sustainable Designmentioning
confidence: 99%